If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -29 = 11 + 4x Reorder the terms: -29 + -1x = 11 + 4x Solving -29 + -1x = 11 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -29 + -1x + -4x = 11 + 4x + -4x Combine like terms: -1x + -4x = -5x -29 + -5x = 11 + 4x + -4x Combine like terms: 4x + -4x = 0 -29 + -5x = 11 + 0 -29 + -5x = 11 Add '29' to each side of the equation. -29 + 29 + -5x = 11 + 29 Combine like terms: -29 + 29 = 0 0 + -5x = 11 + 29 -5x = 11 + 29 Combine like terms: 11 + 29 = 40 -5x = 40 Divide each side by '-5'. x = -8 Simplifying x = -8
| 3x=5(16) | | f(x)=0x^0 | | 3x*x=147 | | 14-2+11+3= | | 5x+15=8x+2 | | 2(d+3)=28 | | f(x)=2x^1+0x^0 | | 15+5z=-10 | | -24-4x=15-x | | 3(m+1)=13 | | f/x | | 2[x-3(0)]= | | 3(5x-2)=4(2x+6) | | 10(c+7)=90 | | -8y+9=13 | | -7(2f+8)=-126 | | f(x)=3x^2+2x^1+0x^0 | | X=(20-2x)*(40-2x) | | 14n+2=72 | | 10(s-5)=-98 | | x=(20-2x)(40-2x) | | f(x)=2senx | | x^4+x^3-8x^2+16x+6=0 | | 225=x^2-16x+68 | | 0=y^2-4y-1 | | 3(3s+6)=72 | | 29+5y-2=15y-13-2y | | x+2x+1+8x-1+3x+2=58 | | 5(t-6)=5 | | F(x)=x-2.5 | | 0.9x=0.9 | | 12x^2-3x=o |